Large social groups as the object of the global psychological impact - Vyacheslav A. Sosnin; Yulia V. Kovaleva (Наука. Культура. Общество, 2022)
The psychological phenomena that are typical for large social groups at the present stage of the information and communication technologies development used for various purposes, including, global geopolitical interests considered. Problems of loss and restoration of social identity as well as the process of updating of large social group Subject status because of information and psychological influence discussed.